RNA Interference against Discoidin Domain Receptor 2 Ameliorates Alcoholic Liver Disease in Rats - Luo, Zheng; Liu, Huimin; Sun, Xiaomeng; Guo, Rong; Cui, Ruibing; Ma, Xiangxing; Yan, Ming (PloS one, 2013)
Discoidin domain receptor 2 (DDR2) is involved in fibrotic disease. However, the exact pathogenic implications of the receptor in early alcoholic liver disease are still controversial. We constructed plasmid vectors encoding short-hairpin RNA against DDR2 to investigate its role in alcoholic liver disease in an immortalized rat hepatic stellate cell line, HSC-T6, and in rats by MTT, RT-PCR and western blot analyses; immunohistochemistry and electron microscopy. Alcohol-induced upregulation of DDR2 was associated with the expression of matrix metalloproteinase 2, the transforming growth factor β1 signaling pathway and tissue inhibitor of metalloproteinase 1; collagen deposition; and extracellular matrix remodeling. Inhibition of DDR2 decreased HSC-T6 cell proliferation and liver injury in rats with 10-week-induced alcoholic liver disease. DDR2 may have an important role in the pathogenesis of early-stage alcoholic liver disease. Silencing DDR2 may be effective in preventing early-stage alcoholic liver disease.